2018
DOI: 10.1515/humo-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

How the Kenyan runner’s body structure affects sports results

Abstract: Purpose. The aim of this study was to determine the dependency between somatic parameters of selected Kenyan marathon runners and results achieved in long-distance runs (marathon, half-marathon, 10,000 meters). Methods. The research study was conducted on a sample of 9 top-level long-distance Kenyan runners whose results in Poland correspond to International Masterclass. All runners' (mean ± SD) age: 23.67 ± 4.41 years, weight: 55.98 ± 4.84 kg, height: 169.18 cm ± 4.15cm. All participants had their anthropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…With respect to the significant correlations, the moderate values observed between the %BF and CMJ variables (r: -0.769) may explain why the values of body composition correlated negatively with performance in the motor test. Considering that many sports show correlations between performance variables and somatic features [29], the negative overload generated by the increase in body composition values affects the execution of the motor gestures and, consequently, jumping impulse force [30]. the correlation between CMJ and dJ (r: -0.713) with increases in explosiveness are verified from the greater height in the CMJ jump when analysing the performance of the subjects in the dJ jump; the highest values of this ability are related to the shorter contact times with the jumping performance, which may have a relation with the time of ground contact during the execution of strides in races.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the significant correlations, the moderate values observed between the %BF and CMJ variables (r: -0.769) may explain why the values of body composition correlated negatively with performance in the motor test. Considering that many sports show correlations between performance variables and somatic features [29], the negative overload generated by the increase in body composition values affects the execution of the motor gestures and, consequently, jumping impulse force [30]. the correlation between CMJ and dJ (r: -0.713) with increases in explosiveness are verified from the greater height in the CMJ jump when analysing the performance of the subjects in the dJ jump; the highest values of this ability are related to the shorter contact times with the jumping performance, which may have a relation with the time of ground contact during the execution of strides in races.…”
Section: Resultsmentioning
confidence: 99%
“…Eksterowicz et al . [ 17 ] found that Marathon finishing-time was positively correlated with upper limb length, torso length, hip width, and waist-hip ratio in a sample of Kenyan endurance runners. More generally, anthropometric features affect stride length, movement stability, air and ground resistance [ 1 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] found that Marathon finishing-time was positively correlated with upper limb length, torso length, hip width, and waist-hip ratio in a sample of Kenyan endurance runners. More generally, anthropometric features affect stride length, movement stability, air and ground resistance [ 1 , 17 , 18 ]. LTBP1 , one of the most differentiated genes for Oromo, participates in the molecular pathway associated with those phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, el pliegue abdominal también se alejó del modelo, estableciendo valores negativos para todas las categorías, tal como los obtenidos por Jorquera et al (2013), en futbolistas chilenos; este último estudio, también encontró valores positivos en el diámetro anteroposterior del tórax y el perímetro de la pierna, tal como la presente investigación. El diámetro del tórax está relacionado con la función pulmonar (Erceg et al, 2011), la cual impacta directamente el desempeño deportivo (Nicks et al, 2009), mientras que un bajo valor en el perímetro de la pierna ayuda en la economía de la carrera (Eksterowicz et al, 2016). Lo anterior toma sentido cuando se analizan las distancias recorridas durante un partido de fútbol, ya que los esfuerzos de baja intensidad predominan por sobre los de alta intensidad (Andrzejewski et al).…”
Section: Composición Corporal Por Posición De Juegounclassified